READING COMPREHENSION AND THE SPECIAL STRATEGIES TO ENHANCE IT - Eshmirzaeva , Nozima Bakhodirovna (Educational Research in Universal Sciences, 2023)
According to some researchers around the world, reading skills play a significant part in the development of our world outlook. That is why, we should develop these skills very well in order to gain sufficient knowledge that we need for variety of reasons in our education process. So comprehension is something which is a vital part of reading. While we are reading, we should do our best to understand and get the gist of what we are reading for better overall awareness. Through learning and using reading strategies and modifying the way we read, it is possible to develop our reading comprehension skills and making what we read more straightforward as well as more interesting. This article will explore what reading comprehension is and provides with the most useful strategies that can be used to improve our reading skills.